The Impact of Government Spending on Service Sector Growth in Indonesia: A VECM Model Approach - Rahmatika, Maula Fadhilata; Zubaidah, Dyah Dwi; Wahyudi, Setyo Tri (Journal of Policy and Sustainable Development Studies, 2026)
The service sector is crucial for economic development in developed and developing countries. However, many developing nations, including Indonesia, face challenges in expanding their service sectors, often underestimating their potential. In line with Keynesian theory, government spending is key to stimulating sectoral growth. This research seeks to address the gap in the existing literature by exploring the relationship between specific government expenditures—on subsidies, education, health, and infrastructure—and the growth of Indonesia's service sector between 1990 and 2019. The study aims to answer the following research questions: (1) how does government spending in these four areas influence the growth of the service sector, and (2) which government spending has a significant impact on service sector growth in the short and long term? Using time-series data from the Indonesian Central Bureau of Statistics and the Ministry of Finance, the study employs the Vector Error Correction Model (VECM) to analyze short-term and long-term effects. The results reveal that government spending in education, subsidies, health, and infrastructure significantly contributes to service sector growth in the long term, while no significant short-term effects are observed.